2012
DOI: 10.1104/pp.111.192104
|View full text |Cite
|
Sign up to set email alerts
|

PoppyAPETALA1/FRUITFULLOrthologs Control Flowering Time, Branching, Perianth Identity, and Fruit Development    

Abstract: Several MADS box gene lineages involved in flower development have undergone duplications that correlate with the diversification of large groups of flowering plants. In the APETALA1 gene lineage, a major duplication coincides with the origin of the core eudicots, resulting in the euFUL and the euAP1 clades. Arabidopsis FRUITFULL (FUL) and APETALA1 (AP1) function redundantly in specifying floral meristem identity but function independently in sepal and petal identity (AP1) and in proper fruit development and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 102 publications
3
100
3
7
Order By: Relevance
“…The A class is the most debated and apparently least evolutionarily conserved homeotic function (Causier et al, 2010). Recent analysis of the function of SQUA subfamily genes from basal eudicots suggests that the 'Afunction' evolved via subfunctionalization after gene duplication(s) at the base of core eudicots from a more broad action of SQUA subfamily members in floral meristem specification, floral organ specification and fruit development [see Pabón-Mora et al (Pabón-Mora et al, 2012) and references therein]. Interestingly, the E function appears to be exerted not only by genes from the SEP subfamily, but also by the closely related AGL6 subfamily, at least in some flowering plant species such as petunia (Vandenbussche et al, 2003b;Rijpkema et al, 2009), rice (Ohmori et al, 2009;Cui et al, 2010;Gao et al, 2010;Li et al, 2011) and maize (Thompson et al, 2009).…”
Section: Flower Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The A class is the most debated and apparently least evolutionarily conserved homeotic function (Causier et al, 2010). Recent analysis of the function of SQUA subfamily genes from basal eudicots suggests that the 'Afunction' evolved via subfunctionalization after gene duplication(s) at the base of core eudicots from a more broad action of SQUA subfamily members in floral meristem specification, floral organ specification and fruit development [see Pabón-Mora et al (Pabón-Mora et al, 2012) and references therein]. Interestingly, the E function appears to be exerted not only by genes from the SEP subfamily, but also by the closely related AGL6 subfamily, at least in some flowering plant species such as petunia (Vandenbussche et al, 2003b;Rijpkema et al, 2009), rice (Ohmori et al, 2009;Cui et al, 2010;Gao et al, 2010;Li et al, 2011) and maize (Thompson et al, 2009).…”
Section: Flower Developmentmentioning
confidence: 99%
“…The MC protein interacts with JOINTLESS (J), a member of the STMADS11 subfamily and a regulator of fruit abscission, to form a functionally active transcription factor complex (Nakano et al, 2012). The multiple roles of SQUA subfamily members in floral transition, axillary meristem growth, perianth identity and fruit development are already evident in the basal eudicot species California poppy and opium poppy (Pabón-Mora et al, 2012). …”
mentioning
confidence: 99%
“…However, the A function is thought to be Brassicaceae specific, and in the asterids petunia and snapdragon, C gene expression is excluded from the perianth by the action of microRNA genes BLIND and FISTULATA, respectively (Cartolano et al, 2007). Interestingly, recent experiments by Pabón-Mora et al (2012) have revealed that expression of the opium poppy AG homolog and reproductive organ identity are expanded when AP1/FUL-like genes are downregulated by VIGS. However, downregulation of the AP1/ FUL-like genes in California poppy had no effect on floral organ identity, indicating that spatial regulation of AG homolog expression is variable among angiosperms (Pabón-Mora et al, 2012).…”
Section: Class Gene Regulation By B Class Genesmentioning
confidence: 99%
“…Interestingly, recent experiments by Pabón-Mora et al (2012) have revealed that expression of the opium poppy AG homolog and reproductive organ identity are expanded when AP1/FUL-like genes are downregulated by VIGS. However, downregulation of the AP1/ FUL-like genes in California poppy had no effect on floral organ identity, indicating that spatial regulation of AG homolog expression is variable among angiosperms (Pabón-Mora et al, 2012).…”
Section: Class Gene Regulation By B Class Genesmentioning
confidence: 99%
“…The recent discovery that a FUL homolog regulates anthocyanin accumulation in the nonclimacteric fruits of bilberry (Jaakola et al, 2010) provides strong evidence for the wide conservation of ripening regulators. The role of FUL in fruits may be even more widely conserved, since the gene is also essential for dry fruit development in Arabidopsis (Ferrándiz et al, 2000) and the basal eudicot poppy (Eschscholzia californica; Pabón-Mora et al, 2012). In this context, it will also be very interesting to determine the regulatory network involved in fruit ripening in Solanaceae species that bear dry capsular fruits, like petunia (Petunia hybrida) and tobacco (Nicotiana tabacum).…”
Section: Ful1 and Ful2 Function Largely Independently Of The Ethylenementioning
confidence: 99%